Modattire.kl / Nur Aina Adriana Azman and Muhammad Shamie Khairulah - Azman, Nur Aina Adriana; Khairulah, Muhammad Shamie (2023)
All Universiti Technology Mara (UiTM) students who further their study at the bachelor level need to take the Principle of Entrepreneurship (ENT530) to understand the guideline and expose students to business orientation. In this course, students will be conducting a written report on a case study business or company. Therefore, from this assignment, we have created a small business called Modattire.kl. Modattire.kl is owned by two owners and works by Nur Aina Adriana Bt Azman and Muhammad Shamie Bin Khairulah. Our business also uses social media which is the Facebook (FB) page as a platform for us to attract online customers, gain more awareness and generate more sales. Therefore, we will promote Modattire.kl by doing Facebook posts such as teaser posts, copywriting hard-sell, and soft-sell as our sale postings. In this social media portfolio assignment, students must have a pair group. Each student has to find a product and utilized Facebook (FB) for an online marketing campaign in small businesses. Thus, students are free to create their own products to be sold online. Modattire.kl with tagline "Labuh, Sejuk &Selesa", all the design chosen is a loose, long dresses, cooling clothes, and minimalist designs. Inspires women to live with more confidence in life and fight passionately for their dreams. The main objective is to achieve sustainable fashion, and our shop also focuses on customers who want to find loose, cooling, and long dresses with minimalist designs and at the same time follow the trend. Our business was started on May 16th, 2023. According to the customer review, our product gave satisfying feedback to the customer because our product quality is well taken care of. Such as fabric quality, and safe packaging and they are happy when receiving it. Modattire.kl’s product is also liked by many people due to its affordable price. Hence, this product provides a good insight for the continuation of sales to our customers.